1994
DOI: 10.4319/lo.1994.39.2.0452
|View full text |Cite
|
Sign up to set email alerts
|

Regional pattern of riverine dissolved organic carbon in the Amazon drainage basin of Bolivia

Abstract: Dissolved organic carbon (DOC) was analyzed at 11 hydrometric stations and 41 Andean and lowland sites in the upper Rio Madeira drainage basin where anthropogenic alteration is low. The two regions, Andes and Llanos, behave very differently. Mean DOC is 2.2 mg liter−1 (range, 1.2–4.2 mg liter−1) in the Andes and 5.7 mg liter−1(range, 4.8–7.4 mg liter−1) in the Llanos. DOC enrichment may occur rapidly as Andean rivers enter the Llanos. The specific DOC export is correlated with the watershed forested area in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 7 publications
3
24
0
1
Order By: Relevance
“…The following discussion is based solely on water compositions observed during a single low-water sampling period (November 1994). Because extents of temporal variation in this study area can be substantial (Guyot et al 1988), the following discussion pertains at present only to the observed state of the Beni system at this one point in time. A synthesis of these concepts within the perspective of the river continuum concept will be presented in the following overview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following discussion is based solely on water compositions observed during a single low-water sampling period (November 1994). Because extents of temporal variation in this study area can be substantial (Guyot et al 1988), the following discussion pertains at present only to the observed state of the Beni system at this one point in time. A synthesis of these concepts within the perspective of the river continuum concept will be presented in the following overview.…”
Section: Discussionmentioning
confidence: 99%
“…The organic compositional uniformity we have observed in previous studies of the lower Amazon River and its major tributaries may result primarily from sampling only higher-order reaches of the drainage network, where downstream contrasts are theoretically minimal ( Vannote et al 1980). If any segments of the Amazon system exhibit variable chemical characteristics, they should be lower-order streams and rivers in the Andean Cordillera (Minshall et al 1985;Leopold 1994), whose organic components have been sparingly quantified (Guyot et al 1992;Guyot and Wasson 1994) and remain uncharacterized in any detail.…”
mentioning
confidence: 99%
“…The Andes divert the humid air coming from the NE to the SE, thus causing heavy rainfall in the Andean foothills where, for example, the Chapare region ( Fig. 1) receives more than 6,000 mm/yr (Guyot & Wasson 1994;Roche & Jauregui 1988;Ronchail et al 2005). The area is affected by a marked seasonality characterized by wet summers with extensive inundations and dry winters.…”
Section: Study Areamentioning
confidence: 99%
“…In catchments at lower latitudes where above-ground biomass constitutes a larger proportion of the catchment carbon pool than in temperate systems, some measure of vegetation carbon pools may need to be taken into account (e.g. Guyot and Wasson, 1994). Rivers and lakes can also eect signi®cant carbon transport from soils to the atmosphere via degassing of soil-respired CO 2 (Kling et al, 1992) and respiration of allochthonous organic carbon within the water column Richey et al, 1988;Hedges et al, 1994).…”
Section: Implications For Environmental Change and Future Workmentioning
confidence: 99%
“…Despite the existence of these large-scale trends, the underlying factors that control exports are still only partially understood. Catchment CCC 0885±6087/97/030325±20 physiography, rainfall, discharge, vegetation and wetland composition of the drainage basin have all been shown to in¯uence aquatic carbon concentrations and losses (Moore, 1987;Rasmussen et al, 1989;Eckhardt and Moore, 1990;Esser and Kohlmaier, 1991;Clair et al, 1994;Guyot and Wasson, 1994). However, excluding the model produced by Esser and Kohlmaier (1991), which made use of a spurious correlation between river discharge and riverine carbon export (Kite, 1989;Clair et al, 1994), attempts to model riverine carbon exports using independent variables have so far been successful at explaining only ca.…”
Section: Introductionmentioning
confidence: 99%